A STUDY ON HRD PRACTICES AND ITS IMPACT ON DOCTORS COMMITMENT IN MULTI SPECIALTY HOSPITALS IN COIMBATORE - Jagajeevan, R (Journal of Contemporary Research in Management (JCRM), 2013)
This dissertation explores the nature of human resource development practices and the impact that would make on the doctors’ commitment towards their hospital. The period of study was from July 2009 to February2010. The hospitals selected for the study where multi-specialty in its operations and are located in Coimbatore city with at least 10 years in existence with a minimum of 300 bed service. Four hospitals of the category were selected for the present research. The research data were collected using HRDEQ (Human Resource Development Effectiveness Questionnaire (Krishnaveni and Ram Kumar 2008). OCS (Organizational Commitment Scale (Meyer and Allen 1991) were adopted and validated to the present study. The list of doctors’ with five years experience with the same hospital was collected from the hospital HR / Administration department, which amounted to 181, Out of which 116 responded to the questionnaire which were used for further analysis. Based on the statistical techniques the current study has found that the human resource development activities are effectively practiced in Hospital Industry. However, there exists difference in implementation of the practices. Similarly, the level of commitment of the doctors’ towards their respective hospitals was also found to be high. The present research has proved that there exists a positive relationship between the effective implementation of HRD practices and level of doctors’ commitment towards the hospital. Specifically, it was found that Role analysis, Performance planning & Performance appraisal makes a significant impact on the overall organizational (Hospital) commitment level. On considering the relationship between HRD practices and organizational commitment, the research has found that the implementation of development oriented practices is likely to make a strong impact on the commitment of the doctors’ towards their hospital. The relationship among the research variables were proved through the structural equation modeling technique. The structural paths were proven based on the model statistics, which implies that the implementation of human resource development practices makes a positive impact on the individual’s commitment towards their hospital. Few structural models were also developed and proved to support the research hypothesis.